2021
DOI: 10.17085/apm.20079
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological strategies to prevent postoperative delirium: a systematic review and network meta-analysis

Abstract: Background: Postoperative delirium (POD) is a condition of cerebral dysfunction and a common complication after surgery. This study aimed to compare and determine the relative efficacy of pharmacological interventions for preventing POD using a network meta-analysis (NMA).Methods: We performed a systematic and comprehensive search to identify and analyze all randomized controlled trials until June 29, 2020, comparing two or more pharmacological interventions, including placebo, to prevent or reduce POD. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…There is a retrospective study of 123 geriatric hip fracture patients ( Connolly et al, 2020 ), which showed that intravenous acetaminophen had reduced the incidence of POD from 32.8 to 15.4% ( p = 0.024). In a 2021 network meta-analysis ( Lee et al, 2021 ), the combination of propofol and acetaminophen was the most successful pharmaceutical strategy with a minimal incidence of POD.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…There is a retrospective study of 123 geriatric hip fracture patients ( Connolly et al, 2020 ), which showed that intravenous acetaminophen had reduced the incidence of POD from 32.8 to 15.4% ( p = 0.024). In a 2021 network meta-analysis ( Lee et al, 2021 ), the combination of propofol and acetaminophen was the most successful pharmaceutical strategy with a minimal incidence of POD.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…These include reducing the number of sedatives and algesia used while surgical procedures, attenuating the immune cascade and inflammatory mediators, and dexmedetomidine making a natural sleep-like sedative stress, which might support to decrease the risk of postoperative delirium. 27 Level 1a…”
Section: Discussionmentioning
confidence: 99%
“…Drug-based treatment for POD does not consider for all clients and is used only for patients who do not respond to non-pharmacological treatments. 27 Level 1a…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we pursue the idea that anesthetics used in humans may also have an impact on learning in single-celled organisms. Postoperative delirium is a common condition after the administration of anesthetics which is characterized by altered consciousness, disorientation, impaired memory, perceptual disturbance, altered psychomotor activity, and altered sleep–wake cycles [ 12 ]. Our results, although preliminary, indicate that propofol—which is known as the “milk of amnesia” [ 13 ]—also depresses learning and memory in Physarum .…”
Section: Introductionmentioning
confidence: 99%